1955
DOI: 10.1113/jphysiol.1955.sp005367
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of the isolated water‐buffalo ureter

Abstract: Since Engelmann (1869) described the movements of ureters in laboratory animals it has been generally accepted that urine is carried straight through from the renal pelvis to the bladder with the aid of peristaltic waves. But Fuchs (1936), who observed the passage of urine stained with indigo carmine down the ureters of rabbits, concluded that upon occasion the ureter forms itself into a series of chambers separated by sphincters. Begg (1946) also holds that the existence of a fixed pattern of chambers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Atropine has no effect on spontaneous contractions at doses which abolish contractions induced by acetylcholine. Most animals species investigated, including cat (Lucas, 1908), dog (Roth, 1917;Malin et al, 1968), pig (Longrigg, 1974a & b;Muschat, 1929), rabbit (Gosling & Waas, 1971), rat (Finberg & Peart, 1970) and water-buffalo (Gould et al, 1955), have been shown to possess excitatory a-adrenoceptors as in human tissue. Less consistent responses have been found when using f3-adrenoceptorand muscarinic-agonists.…”
Section: Effect Of Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atropine has no effect on spontaneous contractions at doses which abolish contractions induced by acetylcholine. Most animals species investigated, including cat (Lucas, 1908), dog (Roth, 1917;Malin et al, 1968), pig (Longrigg, 1974a & b;Muschat, 1929), rabbit (Gosling & Waas, 1971), rat (Finberg & Peart, 1970) and water-buffalo (Gould et al, 1955), have been shown to possess excitatory a-adrenoceptors as in human tissue. Less consistent responses have been found when using f3-adrenoceptorand muscarinic-agonists.…”
Section: Effect Of Drugsmentioning
confidence: 99%
“…Although the adrenoceptors do receive a functional innervation, there is no such innervation of the muscarinic receptors (Longrigg, 1974b). Other species such as dog 0306-5251 82/040461-08 $01.00 and water-buffalo have been shown to respond to muscarinic agonists although 'to a lesser degree than seen with a-adrenoceptor stimulation' (Gould et al, 1955;Malin et al, 1968).…”
Section: Effect Of Drugsmentioning
confidence: 99%